Mapping Out A Case of Auditorsâ€™ Duties to Shareholders (Journal of Governance and Development (JGD), 2009)
The term â€˜auditorâ€™ in Latin, means â€˜to listenâ€™. Nonetheless, when scrutinising the duties of auditors, it reveals that they do not merely listen. They also report to the company, on its accounts. Moreover, the scope of these duties has amplified over recent years. This is due to the changes in the corporate landscape. On the other hand, significant judgments have been laid down by courts across jurisdictions whereby in Re Kingston Cotton Mill Co (No 2) [1896] 2 Ch 673 Lopes LJ stated that â€œ...auditors are watchdogs but not bloodhoundâ€¦â€ and the statement of Cardozo CJ in Ultramares Corporation v Touche (1931) 174 NE 441 that to hold auditors liable results to a case of â€œâ€¦liability of an indeterminate amount for an indeterminate time to an indeterminate classâ€¦â€ In the midst of these, it is pertinent to determine the legal position in Malaysia. Essentially, the current legal framework governing auditors must be reassessed in the wake of the scandals involving auditors both in the domestic and international forefront. The study then examines the legal position in United Kingdom, Australia and New Zealand. The study finally explores the appropriate litmus test in determining the duties of auditors to shareholders.